A new iodate-phosphate Pb2(IO3)(PO4) achieving great improvement in birefringence activated by (IO3)− groups - Zhang, Xiao-Han; Yang, Bing-Ping; Chen, Jin; Hu, Chun-Li; Fang, Zhi; Wang, Zujian; Mao, Jiang-Gao (Chemical communications (Cambridge, England), 2020)
The first divalent-metal iodate-phosphate, Pb2(IO3)(PO4), has been prepared via the strategy of introducing (IO3)− into phosphate. The structure features a unique 3D network where [Pb(IO3)]∞+ and [Pb(PO4)]∞− layers are alternatively interconnected. The birefringence of Pb2(IO3)(PO4) is greatly increased to 0.060 at 1064 nm.